Antimicrobial and Antibiofilm Activity of the Probiotic Strain Streptococcus salivarius K12 against Oral Potential Pathogens - Andrea Stašková; Miriam Sondorová; Radomíra Nemcová; Jana Kačírová; Marián Maďar (MDPI AG, 2021)
Oral probiotics are increasingly used in the harmonization of the oral microbiota in the prevention or therapy of various oral diseases. Investigation of the antimicrobial activity of the bacteriocinogenic strain Streptococcus salivarius K12 against oral pathogens shows promising results, not only in suppressing growth, but also in eliminating biofilm formation. Based on these findings, we decided to investigate the antimicrobial and antibiofilm activity of the neutralized cell-free supernatant (nCFS) of S. salivarius K12 at various concentrations against selected potential oral pathogens under in vitro conditions on polystyrene microtiter plates. The nCFS of S. salivarius K12 significantly reduced growth (p < 0.01) in Streptococcus mutans Clarke with increasing concentration from 15 to 60 mg/mL and also in Staphylococcus hominis 41/6 at a concentration of 60 mg/mL (p < 0.001). Biofilm formation significantly decreased (p < 0.001) in Schaalia odontolytica P10 at nCFS concentrations of 60 and 30 mg/mL. Biofilm inhibition (p < 0.001) was also observed in Enterobacter cloacae 4/2 at a concentration of 60 mg/mL. In Schaalia odontolytica P10 and Enterobacter cloacae 4/2, the nCFS had no effect on their growth.